2021
DOI: 10.15446/revfacmed.v69n3.94520
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of COVID-19 research in Latin America and the Caribbean

Abstract: Introduction: Latin America and the Caribbean (LAC) is one of the regions most affected by the COVID-19 pandemic. Yet, there is scarce literature addressing the research strategies developed in LAC to face COVID-19. Objective: To quantify and assess the production of scientific publications about COVID-19 in 32 countries of LAC between January 1 and July 31,2020.    Materials and methods: Bibliometric study. Scientific papers on COVID-19 conducted in LAC or reporting data pertaining to LAC and published betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
4
0
3
Order By: Relevance
“… 32 Also, national and international investments in technological innovation has not prioritised substance abuse research in Latin America, even though millions of dollars have been invested in the development of rapid response projects. 4 , 33 , 34 As long as health stakeholders, political leaders and clinical practice managers do not highlight substance abuse as part of the scientific priorities in every Latin American country, HCWs will be threatened by substance use without control and prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Also, national and international investments in technological innovation has not prioritised substance abuse research in Latin America, even though millions of dollars have been invested in the development of rapid response projects. 4 , 33 , 34 As long as health stakeholders, political leaders and clinical practice managers do not highlight substance abuse as part of the scientific priorities in every Latin American country, HCWs will be threatened by substance use without control and prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several recent reviews have not reported the impact, effectiveness, and limitations of eLearning in Latin American countries [27,[30][31][32][33]. More studies are needed to understand the effect of COVID-19 on medical education in Latin America (particularly in Peru) since investments and scientific response policies have not prioritized educational aspects during the lockdown [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al (2021) claimed that the USA, UK, Italy and China published the most articles on COVID-19 in children and adolescents. Espinosa et al (2021) concluded that Chile had published the most original articles in Latin America and the Caribbean (LAC). Brazil and Mexico have also published the most non-original articles in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…, Dehghanbanadak et al (2020), Sachini et al (2021), Sa'ed (2021), Chiu et al (2004), Sa'ed (2016), Surulinathi et al (2020), Laksham et al (2020), Danesh and Ghavidel (2020), Sahoo and Pandey (2020),Wang and Hong (2020),Zhai (2020),Okhovati and Arshadi (2021),Oh and Kim (2020),Gupta et al (2021),Espinosa et al (2021) andCallon et al (1986).…”
mentioning
confidence: 99%